(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The Panchayat Raj system, a cornerstone of India’s decentralized governance structure, has been instrumental in empowering local communities and fostering community development. This research paper aims to critically examine the performance of the existing Panchayat Raj system in achieving its primary objective of facilitating community development. The study identifies strengths and weaknesses in the Panchayat Raj system’s performance, shedding light on factors that hinder or enhance community development outcomes. It also examines the role of technology and digital tools in improving transparency, accountability, and overall governance within Panchayat Raj institutions. The findings of the study highlight the system’s positive contributions to community development, such as rural infrastructure development, social welfare programs, and resource allocation for education and healthcare. However, challenges related to financial autonomy, capacity building, political interference, and regional disparities persist, impacting the overall effectiveness of the Panchayat Raj system.